Structural and genomic insights into erythromycin and clindamycin resistance of group B Streptococcus isolates in rural West Virginia, United States - Smith, Annabelle P.; Powell, Lillie M.; Palmer, Amaira M.; Choi, Soo Jeon; Berisio, Rita; Demkowicz, Ryan; Lukomski, Slawomir (Frontiers in Microbiology, 2025)
IntroductionGroup B Streptococcus (GBS) is a leading etiological agent of neonatal sepsis and meningitis, as well as invasive infections that predominately affect adults over 65 and people with comorbidities. The Centers for Disease Control and Prevention’s (CDC) nationwide surveillance has identified rising clindamycin and erythromycin resistance as a concerning level threat for invasive GBS infections. West Virginia (WV) is a rural state outside the CDC catchment area, therefore, we investigated 65 WV-GBS isolates identified in clinical specimens from various sources for serotype distribution, as well as the spectrum and genetic markers of erythromycin and clindamycin resistance.ResultsGBS isolates of serotypes II (27.7%), Ib (23.1%), V (18.5%), Ia (13.8%), III (10.8%), and IV (6.2%), were identified. The mef(A) gene encoding macrolide resistance (M phenotype) was detected in 15.4% isolates. The erm(A) and erm(B) genes that are responsible for the combined erythromycin and clindamycin resistance, which characterizes an MLSB [macrolide, lincosamide, and streptogramin B] resistance phenotype, were detected in 67.7% of WV-GBS isolates; also, 81.4% of those displayed constitutive (cMLSB) and 18.6% inducible (iMLSB) resistance to clindamycin by erythromycin using the D-test. A cluster of mutations within the regulatory region of erm(A) were identified in association with a cMLSB sub-phenotype, whereas most of the erm(B) promoters sequenced from isolates with a cMLSB background lacked analogous sequence polymorphisms. Further, higher erythromycin MIC values were associated with the erm(B) determinant compared with erm(A), while structural models of the GBS-ErmA and GBS-ErmB enzymes show conservation in both SAM- and rRNA-binding sites.SignificanceOur data demonstrate that the 80.0% rate of erythromycin and 70.8% of clindamycin resistance in WV is higher than the national average of 61.7 and 52.5%, respectively, while being widespread across a variety of clinical specimens (urine, throat, respiratory tract, blood, foot ulcers, perisplenic fluid, various wounds, and the rectovaginal area). Providers should be aware of the current threat of antibiotic resistance, especially in “primary care deserts” existing in rural areas such as WV.